The (un)bearable cost of European public debt sustainability - Vale, S.; Camões, F. (5th UECE Conference on Economic and Financial Adjustments, 2016)
The European debt crisis emerged from the 2008 financial crisis, and soon expanded to other economic dimensions. The recession unravelled the fragility of the European integration project, especially by introducing the need to bail-out peripheral countries. Fiscal consolidation was the therapy chosen to deal with over indebtedness that ended decreasing growth and increasing the hurdles to recover and to drop debt-to-GDP ratios. However, the latest decisions by the European Commission claim the imposition of limits to public debt as a necessary and sufficient condition to recover from the crisis and request that countries compromise on running positive budget balances to achieve it, insisting on a model that has shown ineffective. In this paper we study European debt crisis describing the main events that took place from the creation of the single currency to 2014. We discuss how, given the recent requirements to correct fiscal unbalances and to control public debt by forcing its convergence to 60% of GDP in 20 years, the demand over already stressed countries is unsustainable, pushing the European monetary project to a debacle. To test the feasibility of the Treaty requirements in the framework of a single currency, we perform different simulations for more and less adverse scenarios based on these countries recent past performances. Our results show that the burden of debt adjustment impending over Europe is too demanding and hardly attainable, and even if the cumbersome corrections will have to be taken by peripheral countries, there are few European countries that can avoid running primary surpluses to correct debt. In this context, the risk of a downturn contagion is enormous and will impend to protract the crisis and to preclude debt adjustment.